STUDI LITERATUR: KEMANDIRIAN BELAJAR SISWA DAN PEMBELAJARAN KONSTRUKTIVISME DALAM KURIKULUM MERDEKA - Adinda Cahyani; Tian Abdul Aziz (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Realizing the importance of increasing student learning independence, a learning strategy and approach is needed that can encourage students to construct pre-existing knowledge in accordance with the independent curriculum. This research aims to describe the independent curriculum relevant to student learning independence and constructivism learning. The method used is document analysis research or literature study. The results of this study are student learning independence and constructivism learning relevant to the independent curriculum, because all three use a learning approach that emphasizes student involvement in the learning process which affects students' cognitive and affective in learning mathematics.